Die invloed van mangaan op vrugrypwording by Vitis Vinifera L. cv. Pinotage - Barker, Wilma (Wilma Henriette) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 1964.